Strategi Pengembangan Usaha Minyak Kelapa di PCP Rotat - Helena Bite (Peneliti.net, 2022)
The fruit of the coconut plant has a good source of vegetable protein and can be processed into various products that are beneficial to humans and can be used as raw materials for cooking oil. The competitiveness of coconut products today lies in its downstream industry, no longer in primary products, where the added value in coconut oil is the most valuable downstream product of coconut fruit and is widely used as an industrial raw material or as a goring oil. The purpose of the research is to fulfill the strategy of developing coconut oil business in PCP Rotat. 15 respondents took using purposive sampling techniques and using SWOT analysis tools. The results showed that this strategy was created by looking at the strength factors owned by the company and optimized to achieve the opportunities that exist to the maximum. The strength factors used are the quality of the product, the price offered. Opportunity factors used by technological development and supply sustainability